Optimization of nonlocal surface plasma waves - Qian, Cheng (2014)
We implement a finite element simulation for nonlocal surface plasma waves. It is an extension to a conventional simulation of semi-infinite surface plasmon. Based on the hydrodynamic theorem, nonlocal equations are coupled with Maxwell’s Equations, which are implemented in weak form partial differential equations. Besides, a closer view at nonlocal boundary conditions reveals the effect of additional boundary constraint. An extended optimization scheme for nonlocal grating structure is then presented.